Correlation of Body Mass Index (BMI) with age of Menarche in Adolescent Girls (International Journal of Physiology, 2020)
Background: Occurrence of menarche at the earlier age has been attributed to a significant number ofadverse health outcomes. Depression, eating disorders, metabolic syndrome and Type II diabetes mellitushave been identified as the major adverse health related issues. Furthermore in relation to early age ofmenarche has been identified as a risk factor for breast and endometrial cancer due to the increased exposureto estrogen. Hence, it is important to give awareness in adopting healthy eating habits and involving in dailyphysical exercise.Aim: To measure the body mass index in adolescent girls and correlate between the age of menarche andbody mass index in adolescent girls.Methodology: This is cross-sectional study with a sample size of 200 female students between the age groupof 17 – 19 years attending different courses (MBBS, BDS, AHS and BPT) in Melmaruvathur AdhiparasakthiInstitute of Medical Sciences and Research, Melmaruvathur. An informed consent will be obtained fromthe participants. A dietary history will be taken by questionnaire. The anthropometric measurements forcalculating the BMI will be measured using calibrated instruments.Result: The results of this study the statistically significant were seen among the age of menarche andthe BMI, pearson chi-square is 21.876 and p value is 0.009 and also statistical significant was seen whencompared regularity of periods with BMI, pearson chi-square is 10.018 and p value is 0.01. There was nostatistical significant when compared waist-hip ratio with age of menarche and regularity of periods.Conclusion: The age of menarche had a tight connection with BMI. Increase in BMI causes early age ofmenarche. So having increased body fat, increased body weight, high intake of protein, high-calories foodsand sedentary life style causes early age of menarche in young healthy girls.